The effect of open access competition on average rail prices. The case of Milan – Ancona. Issue 3 (December 2016) - Beria, Paolo; Redondi, Renato; Malighetti, Paolo
Abstract: Italy is among the few countries where open-access rail competition exists, and the entry of the newcomer NTV during 2012 radically changed the market conditions. The aim of this paper is to shed some light on the effect of competition on price strategies. To do that, we focused on the period before and after the opening of a new HS direct service between Milano and Ancona. Through a web crawler, we collected available fares, from 30 to 1 days in advance of departure and for 15 months, between September 2013 and December 2014. We statistically analysed the sample i) to estimate the price reactions of the incumbent after the new entry, and ii) to compare the price strategies of the two operators. Results show that the incumbent reduced economy class prices by about 15%. The newcomer is slightly cheaper for bookings well in advance of the departure date, but raises prices in the very last days before departure. Their fare strategy also changed after three months of operations, when they applied lower prices. Finally, we see that Trenitalia does not respond to NTV's prices, whereas the opposite is true, demonstrating that the newcomer is the price-taker in the short-run. Highlights: The effect of head-on competition on a high-speed rail line in Italy has been studied. The entrance of a newcomer has reduced incumbent's economy prices by 20% on average. In the economy segment the newcomer is the price-taker and adapts day-by-day prices. In the business segment, the newcomer is pricing more thanks to its better service.